The Influence of Reciprocity and Trust on Satisfaction of Members of Sharia Cooperatives in Indonesia: A Social Capital Perspective - Bhinekawati, Risa; Yunita, Patria (Sekolah Tinggi Manajemen IPMI, 2024)
Islamic Micro Finance Institution in the form of sharia cooperatives called Baitul Maal wa Tamil or BMT have grown significantly in Indonesia in the past four decades, and have contributed to improvements of livelihood of their members and poverty eradication. Using the social capital theory, this study aims to investigate whether trust and reciprocity are factors that influence satisfaction of members BMTs in Indonesia. The study gathered 200 respondents from eight sharia cooperatives in six provinces of Indonesia. Using multiple regression models, the collected data was tested and further analyzed using SPSS 24.0 Software. This research found that Reciprocity and Trust have a positive and significant influence on the Satisfaction of sharia cooperative members. Sharia cooperative management can apply the results of this research to improve cooperative performance by building mutually beneficial and trusting relationships with its members. The results of this study can be generalized to sharia cooperatives, while the application to conventional cooperatives needs to be further studied. This research provides empirical evidence for the application of Social Capital Theory in explaining the factors influencing the satisfaction of sharia cooperative members that was not studied before.